(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
Scientific Revolution which happened in Europe beginning from 17th to 18th century show the philosophers of science such as Francis Bacon and Immanuel Kant appeared with their ideas to strengthen the scientific methodology. Among the issues being debated is relevance of values towards science. However, different perspectives from these philosophers lead to the dialectic between science and values. This raises a question mark about their arguments and conclusions regarding the issue between science and values. Therefore, this paper aims to identify the outstanding philosophers of science whose involved in such debate from 17th to 18th century AD with their arguments. Next, the paper aims to analyze the relationship among these philosophers and their conception of science and values. Based on the content analysis method used, there are three important findings. First, Francis Bacon, the founder of Western scientific methods reject the practice of confounding superstitions and human biasness in scientific research. Second, there is a clear continuity between the thought of René Descartes, David Hume and Immanuel Kant’s dualism of science, but with different perspectives, i.e. mind-body dualism, fact-value dualism, phenomena-noumena dualism respectively. Third, the arguments of these philosophers of science, especially Kant implied in the concept of value-free scientific research for the following centuries.